Pengaruh Environmental Disclosure dan Environmental Management System Terhadap Kinerja Keuangan: (Studi Empiris Perusahaan Batubara Terdaftar di BEI Periode 2017-2021) - Asri Nabilatul Wahdah; Dwi Jayanti (Universitas Nusantara PGRI Kediri, 2023)
This research aims to show empirically the effect of Environmental Disclosure and Environmental Management Systems on financial performance. The objects of this research is the coal companies listed on the IDX for the 2017-2021 period. Environmental Disclosure in this study is measured using a proportion ratio based on the Global Reporting Initiate (GRI) indicator for the environmental category as many as 34 disclosure items, namely through a comparison of the amount that companies report with the amount that should be reported, the Environmental Management System measured using dummy variable, while the financial performance measurement uses Return on Assets (ROA). The data was collected using purposive sampling as the method. The number of samples is 18 coal companies. Secondary data is used as research data. Analysis of the data using regression analysis with SPSS. The results of the study show that the Environmental Disclosure and the Environmental Management System have no significant effect on financial performance.